Analyzing Returns to Scale Using DEA: A Study at Institutions of Technological Learning in Brazil - Ramos, Rubens E. B.; Ferreira, Getúlio Marques (Revista Gestão da Produção Operações e Sistemas, 2007)
In this article an application of Data Envelopment Analysis DEA is carried out to evaluate the existence of constant or variable returns to scale in the performance of technological learning institutions with an emphasis on high school education. CCR, BCC and Guarantee Region models are tested for a set of 23 Federal Centers for Technological Education of Brazil (CEFETs). DEA is used to test the existence of constant (CCR model) or variable (BCC model) returns to scale, adopting enrollments, the number of entries and the results from the National High School Exam (ENEM) as products, and budget, faculty and faculty degrees as inputs. The main results suggest there are variable returns to scale for budget and faculty, but a constant return for degrees. The theoretical implications of the findings suggest that an analysis of each input should be carried out before modeling the virtual input and choosing the DEA model. Keywords: Performance Evaluation; DEA; Data Envelopment Analysis; Education; Returns to Scale.